A systemic approach to aging in the work context - Ursula M. Staudinger; Catherine E. Bowen (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2011)
In this article we present the interdisciplinary, developmental and systemic approach to the study of work and aging that guides research at the Jacobs Center on Lifelong Learning and Institutional Development (JCLL). We introduce basic principles of adult development including its plasticity, multi-directionality, and embeddedness in contexts. We describe the different dynamic internal (e.g., psychological, physiological) and external contexts (e.g., organizations, labor market institutions) relevant to the work context that influence adult development. We present how the various disciplinary perspectives at the JCLL contribute to a fuller understanding of various contextual systems and their interactions with regard to the work context. Finally, we describe how a systemic approach to research on work and aging can contribute to the creation of work contexts conducive to productive development across the adult lifespan as summarized in the notion of dynamic human resource management. Importantly, we consider a wider notion of 'productivity' that encompasses not only economic aspects but also intellectual, motivational and emotional outputs.
Keywords: 330; berufliche Sozialisation; altersspezifische Faktoren; Altern; psychische Faktoren; physiologische Faktoren; Arbeitsbedingungen; Arbeitsproduktivität; kognitive Fähigkeit; Arbeitsmotivation; emotionale Intelligenz; human resource management; Personalentwicklung; lebenslanges Lernen; altersadäquate Arbeitsplätze; ältere Arbeitnehmer